2018
DOI: 10.3390/toxins10030115
|View full text |Cite
|
Sign up to set email alerts
|

Host and Cropping System Shape the Fusarium Population: 3ADON-Producers Are Ubiquitous in Wheat Whereas NIV-Producers Are More Prevalent in Rice

Abstract: In recent years, Fusarium head blight (FHB) outbreaks have occurred much more frequently in China. The reduction of burning of the preceding crop residues is suggested to contribute to more severe epidemics as it may increase the initial inoculum. In this study, a large number of Fusarium isolates was collected from blighted wheat spikes as well as from rice stubble with perithecia originating from nine sampling sites in five provinces in Southern China. Fusarium asiaticum dominated both wheat and rice populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
5
22
0
Order By: Relevance
“…Types of crops in crop rotation directly or indirectly promote the infection of cereal crops by Fusarium as the Fusarium ‐contaminated debris from the earlier crop can act as a reservoir for subsequent infection. Previous studies associated with FHB in China have shown that the 15ADON chemotype of F. graminearum was dominant in the northeast and Huanghuaihai regions for wheat–maize rotation, the F. asiaticum ‐3ADON was predominant in the Yangtze River region for wheat–rice rotation, and the NIV chemotype of F. asiaticum was the major chemotype in the southwest region for wheat–rice and rice–ratoon rice rotations (Zhang et al , ; Zhang et al , ; Qiu and Shi, ; Dong et al , ; Hao et al , ; Yang et al , ). F. asiaticum with the 3ADON chemotype was the dominant species in wheat, paddy, and weed samples in Jiangsu Province, but the frequencies of NIV producers in weed and paddy samples were approximately three times higher than in wheat in Jiangsu Province (Zhang et al , ; Qiu and Shi, ; Dong et al , ; Yang et al , ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Types of crops in crop rotation directly or indirectly promote the infection of cereal crops by Fusarium as the Fusarium ‐contaminated debris from the earlier crop can act as a reservoir for subsequent infection. Previous studies associated with FHB in China have shown that the 15ADON chemotype of F. graminearum was dominant in the northeast and Huanghuaihai regions for wheat–maize rotation, the F. asiaticum ‐3ADON was predominant in the Yangtze River region for wheat–rice rotation, and the NIV chemotype of F. asiaticum was the major chemotype in the southwest region for wheat–rice and rice–ratoon rice rotations (Zhang et al , ; Zhang et al , ; Qiu and Shi, ; Dong et al , ; Hao et al , ; Yang et al , ). F. asiaticum with the 3ADON chemotype was the dominant species in wheat, paddy, and weed samples in Jiangsu Province, but the frequencies of NIV producers in weed and paddy samples were approximately three times higher than in wheat in Jiangsu Province (Zhang et al , ; Qiu and Shi, ; Dong et al , ; Yang et al , ).…”
Section: Discussionmentioning
confidence: 94%
“…Fusarium graminearum species complex isolates vary in their ability to cause disease in different hosts (Goswami and Kistler, ). In general, both 3ADON and 15ADON chemotypes of F. graminearum and F. asiaticum are more aggressive than NIV chemotypes of F. asiaticum , F. meridionale , and F. cortaderiae in wheat (Starkey et al , ; Spolti et al , ; Umpiérrez‐Failache et al , ; Liu et al , ; Nicolli et al , ; Yang et al , ; Amarasinghe et al , ). However, there have been few reports on the pathogenicity of FGSC isolates in rice (Goswami and Kistler, ; Lee et al , ; Gomes et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary inoculum for host infection is produced on the surface of residues, such as maize stalks, wheat straw and weeds (Pereyra & Dill‐Macky, ). Therefore, anthropogenic activities (crop rotation, tillage and weed management) are key risk factors for Fusarium ‐caused diseases (Leplat et al ., ), where host plant and cropping systems may drive Fusarium population abundance (Leplat et al ., ; Yang et al ., ) and subsequent impact of associated disease.…”
Section: Introductionmentioning
confidence: 99%